MODEL PROJECT BASED LEARNING BERBASIS MEDIA CANVA UNTUK CALON GURU SEKOLAH DASAR - Nasution, Lia Afriyanti (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Education is the endeavour of a person to be a better person and to develop the self-potency that he possesses so that he can benefit himself and others. Education aims to help students to develop and enhance the potential that they possess themselves. Efforts to provide quality, effective and efficient IPA learning are continuing. Starting with the completion of teaching materials, the provision of teachers, up to the continuous updating of curricula – continuous improvements are made, then from that here the researchers carry out the action of creating Media and Teaching Materials by using Canva that produces products to create more innovation, creativity, and activity in the students of prospective SD teachers. Targeted outlets are producing web-based interactive media based on projects or issues, collaborating with partners outside the university on further research, and reputable publications. The research is aimed at studying the application of Project-Based Learning (PjBL) that uses Media Canva in the learning process for prospective teachers of Elementary Schools (SD) at the Faculty of Education and Education Sciences of Muhammadiyah University of Northern Sumatra (UMN) Alwashliyah. The application of this model is expected to enhance the practical skills of prospective teachers in integrating modern learning technologies and media into their teaching practices. The research method used is R n D method. Data is collected through observations, interviews, and document analysis. The participants in this study were students of future SD teachers who were involved in a project-based learning program that uses Canva as the main medium. In addition, the use of Canva as a learning medium enables students to produce interesting and interactive teaching materials, which is expected to increase the interest and motivation of students in the future. The study concludes that the application of the PjBL model based on Media Canva provides significant benefits for the development of pedagogical skills of future SD teachers, as well as making a positive contribution to innovation in educational practice at the Faculty of Education and Science of UMN Alwashliyah.